2018
DOI: 10.30552/ejihpe.v8i1.221
|View full text |Cite
|
Sign up to set email alerts
|

Violencia verbal en el alumnado de Educación Secundaria Obligatoria

Abstract: Existe una creciente alarma social acerca de la violencia verbal por parte de los adolescentes en los centros educativos. El objetivo de estudio es conocer la percepción que tiene el alumnado de Educación Secundaria Obligatoria sobre la violencia verbal dirigida a compañeros y profesorado, identificando factores personales y escolares intervinientes. Se utilizó una metodología cuantitativa con la aplicación del cuestionario de violencia escolar percibida (CUVE-R-ESO) a 4467 alumnos de ESO (M=13.81; DT=1.38). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 3 publications
(3 reference statements)
1
12
0
13
Order By: Relevance
“…These results are coherent with those reported by Judge et al [27], who found significant negative correlations between neuroticism and self-esteem, with an even higher effect size than in our study. The results of the study by Robins et al [28] were similar for the correlations between self-esteem and the extraversion, conscientiousness, and agreeableness dimensions. In their case, they also found a significantly positive but weak association between openness to experience and self-esteem.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…These results are coherent with those reported by Judge et al [27], who found significant negative correlations between neuroticism and self-esteem, with an even higher effect size than in our study. The results of the study by Robins et al [28] were similar for the correlations between self-esteem and the extraversion, conscientiousness, and agreeableness dimensions. In their case, they also found a significantly positive but weak association between openness to experience and self-esteem.…”
Section: Discussionsupporting
confidence: 57%
“…Adolescents are involved in new experiences and sensations, seeking autonomy, differentiation, and personal identity, without their self-regulating mechanisms having yet matured completely [26]. Therefore, a still immature empathy, assertiveness, magical thinking (“that will not happen to me”), and a certain tendency to impulsiveness, which is involved differently in health-risk behaviors [27,28,29,30], characterize adolescents who show a desire for experimentation and innovation, while seeking the approval of friends and schoolmates through the use of ICT.…”
Section: Introductionmentioning
confidence: 99%
“…For example, direct physical aggression refers to hitting someone while stealing would be an example of indirect physical aggression [8]. Direct verbal aggression refers to the insults between the actors involved in such situations, while talking about someone behind their back is considered indirect verbal aggression [9].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to what occurs with verbal violence, studies (in Spain) conclude that it is the pattern of violence most perceived by adolescents [29]. It is prevalent and normalized and not perceived as something alarming [30]. The "Síndic de Greuges" report states that family, teachers and students perceive that verbal violence is most frequent during the school ages [31].…”
Section: Discussionmentioning
confidence: 98%